2021
DOI: 10.20473/brpkm.v1i1.24971
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Academic Stress, Achievement Motivation, dan Perceived Social Support terhadap Academic Burnout Siswa SMK

Abstract: Penelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh academic stress, achievement motivation, dan perceived social support terhadap academic burnout. Metode yang digunakan adalah kuantitatif dengan 103 partisipan siswa SMKN Surabaya. Alat ukur yang digunakan adalah skala adaptasi Educational Stress Scale for Adolescents, karakteristik achievement motivation¸ skala adaptasi Multidimentional Scale of Perceived Social Support, dan skala adaptasi Student Burnout Inventory. Penelitian ini menggunakan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Perceived social support is a cognitive appraisal of individuals regarding social support received. It focuses on assessing the availability or how adequate the asset is, regardless of whether the individual gets that support (López & Cooper, 2011). Dubow & Ullman (1989) revealed that this assessment focuses on the feeling that the individual has someone who cares, loves, respects, and can also be relied on when they need it.…”
Section: Introductionmentioning
confidence: 99%
“…Perceived social support is a cognitive appraisal of individuals regarding social support received. It focuses on assessing the availability or how adequate the asset is, regardless of whether the individual gets that support (López & Cooper, 2011). Dubow & Ullman (1989) revealed that this assessment focuses on the feeling that the individual has someone who cares, loves, respects, and can also be relied on when they need it.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been carried out around this topic but there is still some room for further exploration (Christiana, 2020;Firdaus et al, 2021;Herlin and Darminto, 2020;Putri and Ariana, 2021;Rochmawati et al, 2021;Transiana et al, 2021;Trisnawati, 2020;Winahyu and Wiryosutomo, 2020). Specific observation in the present study is the fact that the burnout phenomenon actually occurs in the Indonesian education sector, especially at the school principal level.…”
Section: Introductionmentioning
confidence: 99%
“…Academic burnout is defined as feeling tired due to study demands, avoidance of existing tasks, and feelings of incompetence as a student (Schaufeli, et al, 2002;Oktasari et al, 2022). Yang (2004deep Ashsari, 2022;Transiana, 2019) explaining the aspects of academic burnout there are three, namely: 1) emotional anxiety, caused by excessive emotional and psychological demands and usually side by side with feelings of frustration and tension. 2) areluctance to study or cynicism, referring to insensitivity or cynical attitude towards the work at hand.…”
Section: Introductionmentioning
confidence: 99%